Higher-order infinite horizon variational problems in discrete quantum calculus - Martins, N.
We obtain necessary optimality conditions for higher-order infinite horizon problems of the calculus of variations via discrete quantum operators. © 2012 Elsevier Ltd. All rights reserved.